Stroke Caused by a Pulmonary Vein Thrombosis Revealing a Metastatic Choriocarcinoma. Issue 23 (9th June 2015) - Bonnet, Louise; Raposo, Nicolas; Blot-Souletie, Nathalie; Faruch Bilfeld, Marie; Chollet, François; Mazière, Julien; Olivot, Jean-Marc; Albucher, Jean-François
Abstract : Supplemental Digital Content is available in the text.